1998
DOI: 10.1093/nar/26.10.2407
|View full text |Cite
|
Sign up to set email alerts
|

High level transactivation by the ecdysone receptor complex at the core recognition motif

Abstract: Ecdysteroid signaling in insects is mediated by the ecdysone receptor complex that is composed of a heterodimer of the ecdysone receptor and Ultraspiracle. The DNA binding specificity plays a critical role of defining the repertoire of target genes that respond to the hormone. We report here the determination of the preferred core recognition motif by a binding site selection procedure. The consensus sequence consists of a perfect palindrome of the heptameric half-site sequence GAGGTCA that is separated by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 46 publications
0
62
0
Order By: Relevance
“…High stringency EMSAs were performed as described under "Experimental Procedures." the SAAB technique) by the related EcR⅐USP complex from Drosophila (38) and sequences shown to bind Mosquito EcR/ USP with high affinity (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…High stringency EMSAs were performed as described under "Experimental Procedures." the SAAB technique) by the related EcR⅐USP complex from Drosophila (38) and sequences shown to bind Mosquito EcR/ USP with high affinity (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Putative sites were filtered using the cutoff Patser score $8.0 (Hertz and Stormo 1999). The following sequences are known binding sites for ECR_USP Scholnick et al 1986;Riddihough and Pelham 1987;Cherbas et al 1991;Antoniewski et al 1993;Vogtli et al 1998;Petersen et al 2003): 59-GGTTGAA TGAATT-39, 59-CGGTCATTGGCCG-39, 59-AGTTCGAGGCACC-39, 59-GTTTCAGTGAAAG-39, 59-GGGTCAATAGCCG-39, 59-CGTTGA ATCAATG-39, 59-ATTTCTTTGAATT-39, 59-GGTTCAATGCACT-39, 59-GGGTTCATGCACT-39, and 59-AGTTCAGCGGCTG-39.…”
Section: Motif Analysismentioning
confidence: 99%
“…The functional EcR is commonly considered as a heterodimer consisting of two proteins, EcR and USP, yet our results clearly demonstrated that AaEcR alone, without USP, can function as a transactivator in yeast, in agreement with results obtained from DmEcR (Dela Cruz & Mak 1997). In vitro transcribed DmEcR (Vogtli et al 1998) and AaEcR (S F Wang and A S Raikhel, unpublished data) are able to bind DNA without USP. It is also conceivable that the EcR homodimer is able to communicate with yeast basal transcription machinery independently of the ligand.…”
Section: Role Of Other Co-activators/co-repressors In the Ligand-depementioning
confidence: 99%